From Passive to Active Electronic Healthcare Records - Bisbal, J.; Grimson, J.; Grimson, W.; Berry, D.; Hederman, L. (Methods of Information in Medicine, 2003)
Objectives: The provision of patient data to clinicians as and when it becomes available is a general objective of information systems in healthcare. It is known that the timely receipt of patient data can have a significant bearing on healthcare outcomes. One of the on-going tasks is to provide this data in the form of an Electronic Healthcare Record according to some agreed standard. The aim in this paper is to provide patient data in electronic form by pushing the information to the end users as soon it becomes available, in advance of any explicit request from the users.Methods: This paper describes how an existing record system, the Synapses Federated Healthcare Records Server, has been extended to incorporate active functionality to facilitate pushing the information to end-user applications. The user must specify the information of interest to him, so that the system pushes only information useful to the final user. The approach proposed here relies solely on the use of callbacks through the middleware layer being used, a mechanism available in all existing middleware implementations.Results: The Synapses Federated Healthcare Records Server which has resulted from this research is a more flexible and scaleable system, capable of fulfilling the needs of a wider range of healthcare organisation than when a strictly passive approach is used.Conclusions: It is shown that healthcare organisation can incorporate a healthcare record system with active functionality without any large investment or significant risk to their existing information systems.
Keywords: Electronic health record; electronic patient record; active database; clinical guideline